The risk factors, antimicrobial resistance patterns, and outcomes associated with extended-spectrum β-lactamases-Producing pathogens in pediatric urinary tract infection - Xin-Tian He; Chia-Ning Chang; Chia-Hsiang Yu; Chih-Chien Wang (Pediatrics and Neonatology)
Background: Extended-spectrum β-lactamases-producing Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis (ESBL-producing-EKP) are an increasingly common cause of childhood urinary tract infection (UTI) worldwide. Recognizing the risk factors and antimicrobial resistance patterns may guide new management in this population. Methods: This is a retrospective cohort study of over 5 years in Taiwan (2017–2021). Inclusion criteria are hospitalized pediatric patients with the discharge diagnosis of UTI caused by E. coli, Klebsiella pneumoniae, or Proteus mirabilis. ESBL-producing-EKP and non-ESBL-producing-EKP UTI cases were reviewed for characteristics, urinary isolate antibiotics resistance, and clinical outcomes. Results: The incidence rate of ESBL-producing-EKP UTI increased over the study period (Overall incidence rate: 14.1 %, 46/327 patients). Recent antibiotic therapy in ≤6 months (X2 = 11.83, p < 0.01) and a preterm gestational history (X2 = 8.11, p < 0.05) were associated with an increased risk. The proportion of patients with these two risk factors for ESBL acquisition were 37.5 % (X2 = 9.08, p < 0.05). The co-resistance rate of ESBL-producing-EKP to other antimicrobial agents was 63.0 % for gentamicin, 56.5 % for trimethoprim-sulfamethoxazole, 52.2 % for ciprofloxacin, 4.3 % for amikacin, and 2.2 % for imipenem. The generalized linear model analysis identified a significantly longer length of stay (β: 2.85; 95 % confidence interval [CI]: 1.14–4.56; p < 0.01) and intensive care unit duration (β: 5.86; 95 % CI: 1.59–10.12; p < 0.01) among patients with ESBL-producing-EKP UTI. Conclusion: Amikacin should be considered as an alternative antimicrobial choice beyond carbapenems for ESBL-producing-EKP UTI, especially in the context of carbapenem-resistant E. coli/Klebsiella pneumoniae (CRE/CRKP) emergence.